Towards curbing global village warming: Nepal’s contribution to make a difference - Poudyal, Diwakar (Journal of Agriculture and Environment, 2007)
The global warming has substantial direct and indirect impact on us, on the health of ecosystems and food and water sources. Warming has been rapid due to economic development with little care on the consequences toward mother earth's atmosphere, land and water systems. Lessons to Nepal include warming of snowy peaks, their quick melting and sooner depletion of snow stocks; increased probability of sudden floods and desertification, changing crop zones; productivity regimes, patterns, maturity days, ecology; insects, predators, diseases their degree of occurrence, types or characteristics etc., so that concerns and priorities to research would be changed. Planting a tree in the backyard, practicing better urban disposals systems, encouraging individual choices such as un plugging a freezer, replacing incandescent bulbs with more efficient ones, sealing and insulating heating and cooling devices and food boxes, using solar, wind or geo-thermal resources whenever possible, joining a group of bicyclists, or mass transit; or resistance to an extreme weather, fuel use for cooking or warming food all can make a difference. It was felt that a single country can do little, but even the little would be of great value. Nepal can help reduce global warming by taking steps such as harnessing river systems soon for clean energy and offer benefits to the global community through safeguarded bio-diversity to maintain genetic system. Nepal should adapt to the bio-secure initiatives for meeting food needs locally and needs to let policymakers and leaders know and win confidence to this concern with support on study on Glaciers in Nepal and monitor the global warming situation and contribute by further seeking realistic small ways to reduce global warming. We can control hazards by raising awareness and exploring smaller and practical approaches at grass root level. The Journal of AGRICULTURE AND ENVIRONMENT Vol. 8, 2007, pp. 133-144